A Case of Acute Leukemia Following Remission of COVID-19 Infection; an Urge to Search for a Probable Association - Nekooghadam, Seyyed Mojtaba; Moradi, Afshin; Karimi Toudeshki, Kimia; Pishgahi, Mehdi (Archives of Academic Emergency Medicine, 2021)
Abstract: Many aspects of Covid-19 infection, especially its complications and long-term health consequences are still unknown. Several reports concerning concomitant covid-19 infection and hematological disorders have been published recently. We aim to present a unique case of acute myeloid leukemia in a 61-year-old man with a previous history of covid-19 infection 40 days ago, with near complete resolution of signs and symptoms attributable to covid-19 infection. After 3 weeks, the patient presented again with progressive weakness, nausea, vomiting, and epigastric pain. No evidence of active covid-19 infection was observed. Instead, remarkable drop of hemoglobin and platelets relative to the values recorded in the discharge notes of the patient was observed. Further workup of the patient revealed evidence of acute leukemia and severe bone marrow involvement. We decided to present the current case as a concerning probable association.